Evaluation of Intercropping and Tobacco Leaf Extract for Management of Fruit Borer (Helicoverpa armigera) and Some Associated Beneficial Insects on Tomato in Eastern Hararghe, Ethiopia - Dabalo, Belachew (Journal of Biology and Life Science, 2024)
Tomato production is challenged by different insect pests among these, fruit borer is the most destructing pests of tomato. To tackle these problems, the study was initiated with the objective to evaluate intercropping and tobacco extract on fruit borer and some associated beneficial insects on tomato in Eastern Hararghe. Head cabbage, common bean, onion, tobacco leaf extract and karate were used as treatments. The experiment was laid out in RCBD with four replications. From these results, significant differences were observed between treatments on larval population per plant and infestation per plant for all insect pests tested and also in population reduction. Tobacco leaf extract highly reduced the population occurrence and infestation level of fruit borer next to karate and followed by onion intercropping. The number of branches, number of fruits, and number of damaged fruits, marketable yield, non-marketable yield, and total yield also showed a significant difference (P < 0.05) among the treatments. The number of fruits per plant, marketable yield, and Total yield were the highest on onion intercrops followed by karate and tobacco extracts whereas the lowest number was observed from head cabbage intercrops. Maximum yield and yield traits were recorded on tomato onion intercropping compared to the rests of intercrops while the botanical extract comparably maximized the yields with Karate. Therefore, tomato-onion intercropping and tobacco leaf extract were used as the best alternatives to karate, the synthetic insecticides in the management of tomato fruit borer.